Remuneration of Non-Life Insurance Intermediaries in the U.K. - Jaques, Andrew James Shaw (2007)
The paper examines possible methods of non-life insurance intermediary remuneration in the context of their regulation by the Financial Services Authority. It examines whether this remuneration needs to be completely transparent given the issues of the potential principal-agent problem that exists in the relationship and whether one 'best fit' approach exists.